The revision and validation of Havighurst’s social roles research - Waynne James; Howard Abney Jr.; M. Suzanne Kirkman; Lynn Dye; Kathleen Hargiss; Nancy Wall (Adult Education Research Conference, 1996)
Historical Context of Havighurst’s Social Role Research Identification of Major Social Roles for the 1990s Developing an Assessment Process for the Identified Roles Findings Based on Gender, Age, and Socioeconomic Level Implications of the Social Role Research Social Role Research : What’s Needed Next